FACTORS AFFECTING THE ECONOMIC POTENTIAL OF THE INDUSTRIAL SECTOR AND METHODS FOR ITS ASSESSMENT (World Economics and Finance Bulletin, 2026)
This article details the factors representing the economic potential of the industrial sector and the econometric approaches used to evaluate them. A classification of econometric modeling of socio-economic processes and a mechanism for analyzing industrial production have been developed. In addition, priority directions for improving economic indicators and its further development in assessing the potential of the industrial sector are proposed
Keywords: Industry; economic-mathematical methods; econometric model